Culture and regional economic development: Evidence from China1. (June 2014) - Shi, Shuxing; Huang, Kunming; Ye, Dezhu; Yu, Linhui
Abstract Empirical research on the determinants of regional economic development typically neglects the influence of culture. This study fills that gap by attempting to establish a causal linkage between culture and economic development in the Chinese context. Our empirical analyses are based on a comprehensive economic statistics of China's provinces and prefectures during 1978 to 2008. We use Protestantism as a proxy for culture because Protestant ethic has been linked to the spirit of capitalism and commercial culture in Weber's famous work. To isolate the exogenous variation in culture measure, historical Protestant dissemination is employed as instruments. The estimation results suggest that Christian commercial culture has a significantly positive impact on economic performance – per capita GDP after other important influences (i.e., capital, population, human resources, institutional quality, trade, infrastructure, geography, etc.) are controlled for. We also find heterogeneous effects of culture on economic development in different regions of China.